Data from Investigating Variation in Replicability: A "Many Labs" Replication Project. Issue 1 (4th April 2014) - Klein, Richard A.; Ratliff, Kate A.; Vianello, Michelangelo; Adams, Reginald B.; Bahník, Štěpán; Bernstein, Michael J.; Bocian, Konrad; Brandt, Mark J.; Brooks, Beach; Brumbaugh, Claudia Chloe; Cemalcilar, Zeynep; Chandler, Jesse; et al.
This dataset is from the Many Labs Replication Project [1 ] in which 13 effects were replicated across 36 samples and over 6, 000 participants. Data from the replications are included, along with demographic variables about the participants and contextual information about the environment in which the replication was conducted. Data were collected in-lab and online through a standardized procedure administered via an online link. The dataset is stored on the Open Science Framework website. These data could be used to further investigate the results of the included 13 effects or to study replication and generalizability more broadly.